Introduction of GIS software (Geographical information system) as a life Teachers and Students / imedium School for Namira Medan - Kadreni, Emilia; Mulia, Ahmad Perwira; Pandia, Indra Jaya; Harahap, Hamidah; Manurung, Renita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Namira High School is one of the favorite schools in the city of Medan, with the number of students graduating and being accepted at the State University increasing from year to year. To further foster and improve the quality and creativity of Namira High School Students and Teachers, a technology-based training program for the Geographical Information System (GIS). Community Service Program is part of the Tri Dharma College, in collaboration with High School partners Namira, is expected to be able to increase learning in the Computer Laboratory to learn the concepts and technology of GIS which is relatively new. By attending this training, students get the opportunity to work more by utilizing geospatial-based information. The use of Geographical Information System (GIS) in various fields is very real, because GIS provides various facilities that are relatively easy to do. With the open source GIS software training, it is hoped that students and teachers at Namira High School will know the importance of geography literacy and its use in various fields.